2015
DOI: 10.1002/hep.27409
|View full text |Cite
|
Sign up to set email alerts
|

Perilipin 5 improves hepatic lipotoxicity by inhibiting lipolysis

Abstract: Abnormal metabolism of nonesterified fatty acids (NEFAs) and their derivatives has been reported to be the main cause of intracellular lipotoxic injury. Normally, NEFAs are stored in lipid droplets (LDs) in the form of triglyceride (TG), which could reduce the lipotoxicity of cytosolic NEFAs. Previous studies have implicated that Perilipin 5 (Plin5), an LD‐binding protein, regulates the storage and hydrolysis of TG in LD. However, its roles and underlying mechanisms in the liver remain unknown. Here we found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
189
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 174 publications
(209 citation statements)
references
References 31 publications
17
189
3
Order By: Relevance
“…Similar to the heart, Plin5 deficiency also interferes with TG homeostasis in the liver, leading to a reduction in hepatic TG content and LD size (9). In accordance with these findings, Plin5-enriched LDs, either derived from cardiac tissue of CM-Plin5 mice or from COS-7 cells overexpressing recombinant Plin5, were resistant toward TG breakdown in vitro (26) suggesting that Plin5 acts as a lipolytic barrier.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Similar to the heart, Plin5 deficiency also interferes with TG homeostasis in the liver, leading to a reduction in hepatic TG content and LD size (9). In accordance with these findings, Plin5-enriched LDs, either derived from cardiac tissue of CM-Plin5 mice or from COS-7 cells overexpressing recombinant Plin5, were resistant toward TG breakdown in vitro (26) suggesting that Plin5 acts as a lipolytic barrier.…”
Section: Discussionsupporting
confidence: 67%
“…Similar to Plin1, CGI-58 is also recruited by Plin5 at the LD surface (19 -21), suggesting that Plin5 may exert a similar role in the regulation of lipolysis in non-AT. A very recent study exploring the impact of Plin5 deficiency on hepatic TG metabolism demonstrated that increasing concentrations of Plin5 counteract ATGL and CGI-58 interactions, whereas the absence of Plin5 stimulates lipolysis in the presence of CGI-58 and ATGL (9). These findings further suggest that Plin5 controls lipolysis via recruiting or releasing CGI-58.…”
Section: Discussionmentioning
confidence: 89%
“…4,5 Recent work in Plin5 knockout mice suggests a role in high fat diet (HFD)-induced hepatic lipotoxicity. 6 Hepatic fibrosis refers to the deposition of high-density extracellular matrix (ECM) protein forming scarring tissue due to an imbalance between fibrogenesis and fibrolysis. Liver fibrosis and in particular cirrhosis have become major endpoints in clinical trials of patients with chronic liver diseases.…”
mentioning
confidence: 99%
“…PLIN5 KO mice also developed cardiac dysfunction. The PLIN5 KO animal displayed reduced hepatic steatosis with increased mitochondrial proliferation, lipotoxic injury in the hepatocytes [40]. Interestingly, overexpression of PLIN5…”
Section: Accumulation In Hepatocytesmentioning
confidence: 96%
“…PLIN5 stabilizes lipid droplets by sequestrating faty acids, and because PLIN5 can recruit mitochondria to lipid droplet surface, it facilitates to release faty acids to mitochondria for the oxidation [39]. Given its gatekeeper roles on the lipid oxidation, it has been suggested that PLIN5 could protect cardiac myocytes and hepatocytes from oxidative stress [38,40]. PLIN5 leads several modiications on the lipid metabolism as well as insulin sensitivity, and details are discussed in a separate paragraph.…”
Section: Plin5mentioning
confidence: 99%